1992
DOI: 10.1037/0022-006x.60.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and the pain-mood relation in rheumatoid arthritis: Insights from a prospective daily study.

Abstract: For 75 consecutive days, 54 Ss with rheumatoid arthritis supplied daily reports of their mood and joint pain. After aggregating daily reports, the relation between chronic mood and chronic pain remained statistically significant when controlling for neuroticism, depression, disease activity, disability, and characteristic responses to increasing pain. Findings of a path analysis suggest that (a) individuals higher in neuroticism experience more chronic distress regardless of their responses to pain, their pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
3
5

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(168 citation statements)
references
References 38 publications
10
149
3
5
Order By: Relevance
“…Some studies of individuals coping with other MANNE AND ZAUTRA life stressors have suggested that certain personality traits, including neuroticism, predict coping choices (36). For example, in arthritis patients, internal locus of control has been related to active coping (17) and neuroticism has been associated with wishful thinking and catastrophizing (37). Bolger (36) sees these findings as evidence that coping is a personality process that actualizes dispositional differences during encounters with stressful events.…”
Section: Issues Of Methodology and Theorymentioning
confidence: 99%
“…Some studies of individuals coping with other MANNE AND ZAUTRA life stressors have suggested that certain personality traits, including neuroticism, predict coping choices (36). For example, in arthritis patients, internal locus of control has been related to active coping (17) and neuroticism has been associated with wishful thinking and catastrophizing (37). Bolger (36) sees these findings as evidence that coping is a personality process that actualizes dispositional differences during encounters with stressful events.…”
Section: Issues Of Methodology and Theorymentioning
confidence: 99%
“…In a previous study, we found internal consistencies for the neuroticism subscales ranged from 0.72 to 0.83 and a principal components analysis identified a single factor with an eigenvalue of 3.63 that loaded higher than 0.5 on each of the subscales. Patients scoring higher on this measure reported more depressive symptoms and pain, and more disturbed daily mood independent of their pain (32). Neuroticism scores also correlate with somatic complaints, but not with more objective indicators of disease (31).…”
Section: Methodsmentioning
confidence: 85%
“…In Affleck et al's (1992a) study, high neuroticism individuals showed lower correlations between reports of pain and mood, indicating that the distress reported by individuals high in neuroticism is partly independent of pain. Lombardo, Tan, Jensen, & Anderson (2005) expected low self-efficacy to be related to high maladaptive anger management, but found that this relation holds only at low pain levels, while at high pain intensity there were no differences in anger management between low and high self-efficacy.…”
Section: Coping and Emotion Regulation -Context-dependence In Chronicmentioning
confidence: 87%
“…In a heterogeneous sample, pain catastrophizing amplified the relation between focusing attention on pain and pain threshold and tolerance during an experimental coldpressor task, but not pain reporting (Michael and Burns, 2004). Affleck, Tennen, Urrows, & Higgins (1992a) showed that increased neuroticism led to lower correlations between pain and mood, while illness duration, disability, disease activity and average daily pain all led to higher pain-mood correlations. To anticipate, these opposite results are consistent with the desynchrony phenomenon discussed in section six.…”
Section: Generalized Discrimination Ability -Separating Pain From Itsmentioning
confidence: 99%
See 1 more Smart Citation